Gender and Judging in Portugal: Opinions and Perceptions - Duarte, Madalena (2016)
In Portugal, the phenomenon of feminization of the legal professions is quite recent compared to other countries. The increasing predominance of women among magistrates – judges and public prosecutors – since 2006 has been overwhelming though. If, until 1974, the judiciary was forbidden to women, in 2015, from a total of 1990 judges in first instance courts, Appeal Courts and the Judicial Supreme Court and the Administrative Supreme Court, 1175 were women (59%). Within the Public Prosecution, 61% were women. The weight of women in the legal professions is visible, even, at the Centre for Judicial Studies, where 67,5% of the justice auditors, in 2014, were women. In this scenario, the aim of this article is to discuss the representations of the legal professionals, on the repercussions of this change to the judiciary and to the legal culture in Portugal.